The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jmedchem.1c00117
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Preclinical Evaluation, and First-in-Human PET Study of Quinoline-Containing PSMA Tracers with Decreased Renal Excretion

Abstract: The prostate-specific membrane antigen (PSMA) is considered to be an excellent theranostic target of prostate cancer (PCa). In this study, three 18 F-labeled PSMA tracers with a more lipophilic quinoline functional spacer were designed, synthesized, and evaluated based on the Glu-Ureido-Lys binding motif. The effect of structure-related lipophilic difference on distribution and excretion of these tracers in vitro and in vivo (cells, rodent, primate, and human) was investigated by comparing with [ 18 F]DCFPyL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Moreover, a lipophilic character of the tracer can increase nonspecific uptake in other organs. 20 , 22 24 , 28 In the case of PSMA ligands, higher ligand lipophilicity of PSMA-I&T-based ligands led to an increase in tumor uptake in LNCaP xenografts. 24 In addition, Böhmer et al developed and characterized a copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) based PSMA ligand for PET imaging called [ 18 F]PSMA-MIC01.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a lipophilic character of the tracer can increase nonspecific uptake in other organs. 20 , 22 24 , 28 In the case of PSMA ligands, higher ligand lipophilicity of PSMA-I&T-based ligands led to an increase in tumor uptake in LNCaP xenografts. 24 In addition, Böhmer et al developed and characterized a copper(I)-catalyzed azide–alkyne cycloaddition (CuAAC) based PSMA ligand for PET imaging called [ 18 F]PSMA-MIC01.…”
Section: Discussionmentioning
confidence: 99%
“…aromatics such as in dibenzocyclooctene), is prone to increase the fraction of slow hepatobiliary clearance [29]. In addition, the study of Zhang et al showed that addition of lipophilic quinoline groups in PSMA ligand [ 18 F]DCFPyl led to a large increase in liver accumulation in mice, primates and PCa patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Vaidyanathan et al demonstrated further improvements in the biodistribution and pharmacokinetic profile by adding a guanidino group to the aromatic ring of the inhibitor [82]. In addition, modifications with quinolone derivatives appear advantageous in diagnostic tracers and could potentially serve as templates for future therapeutic approaches [83].…”
Section: Linkers and Chelatorsmentioning
confidence: 99%